DePhine – The Deimos and Phobos Interior Explorer. Issue 8 (15th October 2018) - Oberst, Jürgen; Wickhusen, Kai; Willner, Konrad; Gwinner, Klaus; Spiridonova, Sofya; Kahle, Ralph; Coates, Andrew; Herique, Alain; Plettemeier, Dirk; Díaz-Michelena, Marina; Zakharov, Alexander; Futaana, Yoshifumi; et al.
Abstract: DePhine – Deimos and Phobos Interior Explorer – is a mission proposed in the context of ESA's Cosmic Vision program, for launch in 2030. The mission will explore the origin and the evolution of the two Martian satellites, by focusing on their interior structures and diversity, by addressing the following open questions: Are Phobos and Deimos true siblings, originating from the same source and sharing the same formation scenario? Are the satellites rubble piles or solid bodies? Do they possess hidden deposits of water ice in their interiors? The DePhine spacecraft will be inserted into Mars transfer and will initially enter a Deimos quasi-satellite orbit to carry out a comprehensive global mapping. The goal is to obtain physical parameters and remote sensing data for Deimos comparable to data expected to be available for Phobos at the time of the DePhine mission for comparative studies. As a highlight of the mission, close flybys will be performed at low velocities, which will increase data integration times, enhance the signal strength and data resolution. 10–20 flyby sequences, including polar passes, will result in a dense global grid of observation tracks. The spacecraft orbit will then be changed into a Phobos resonance orbit to carry out multiple close flybys and to perform similar remote sensing as for Deimos. The spacecraft will carry a suite of remote sensing instruments, including a camera system, a radio science experiment, a high-frequency radar, a magnetometer, and a Gamma Ray/Neutron Detector. A steerable antenna will allow simultaneous radio tracking and remote sensing observations (which is technically not possible for Mars Express). Additional instrumentation, e.g. a dust detector and a solar wind sensor, will address further science goals of the mission. If Ariane 6–2 and higher lift performance are available for launch (the baseline mission assumes a launch on a Soyuz Fregat), we expect to have greater spacecraft mobility and possibly added payloads.